MORFOLOGI BUAH DAN BIJI RAFFLESIA PATMA DAN R. ARNOLDII - Mursidawati, Sofi (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2012)
Most members of family Rafflesiaceae are rare plants which found only in a restricted area in Southeast Asia. As a holoparasitic plant Rafflesia totally depends on the specific host plant in specific habitat. The rarity of Rafflesia caused the limited number of research of many biological aspects of this species. In this study, observations on the fruit and seed of R. patma and R. arnoldii were carried out in its habitat and laboratory. Figures and dimension of the seeds was recorded by Scanning Electron Microscope (SEM).